Advances in library administration and organization. Vol. 17 - Williams, Delmus Eugene; Garten, Edward (Emerald, 2000)
Advances in Library Administration and Organization, since its inception in 1982, has had as its primary aim the provision of a forum for research articles of interest to library managers that are longer than the typical journal article but shorter than most books in library administration. Over the years, ALAO has been successful in allowing more experienced managers to discuss fully topics that interest them and in identifying scholars who are talking about issues that are of importance to all library administrators. From the outset, ALAO's mix of contributions to the literature of library administration and organization was intended to be both diverse and eclectic. Now in its 17th year ALAO has remained true to its purpose. The series is widely read by practitioners, library and information science graduate students, and those working in associated fields of information management. ALAO remains the premier monographic series in library administration and organization.
Includes index.
Keywords: Library administration.; elektronické knihy; electronic books